Duethe Heir’s Oral Will of the Heirth before the Tradition of Batak Toba Instruction Happened on the Instructed Land - Imman Yusuf Sitinjak; Humala Sitinjak; Sariaman Gultom (Budapest International Research and Critics University, 2021)
This research aims to identify and discuss the problems and symptoms that occur when death and open inheritance occurs, while the will of the heir has been said verbally to the heirs in the traditional inheritance of Batak Toba. This research discusses the problems that arise when the traditional inheritance of Batak Toba is carried out and there is a verbal will by the heir, especially in the heir's land ownership. The problem that arises when open inheritance is carried out in customary inheritance is a dispute from the heirs who are dissatisfied with the unequal distribution to the heirs, while the heirs who get a portie in inheritance are boys, while for women it is a form of gift given male heirs to girls. In the event of a dispute over inherited land, when the name of the land is transferred to the BPN office, there will be obstacles.